Extremely Preterm Infant Born to a Mother With Severe COVID-19 Pneumonia - Molly C. Easterlin MD, MS; Theodore De Beritto MD, MS; Amy M. Yeh MD, MPH; Fiona B. Wertheimer DO; Rangasamy Ramanathan MD (SAGE Publishing, 2020)
Little is known about the effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on pregnant women, fetuses, and neonates, especially when the virus is contracted early in pregnancy. The literature is especially lacking on the effects of SARS-CoV-2 on extremely preterm (<28 weeks gestation) infants who have underdeveloped immune systems. We report the case of an extremely preterm, 25-week 5-days old infant, born to a mother with severe COVID-19 (coronavirus disease-2019) pneumonia. In this case, there is no evidence of vertical transmission of SARS-CoV-2 based on reverse transcription-polymerase chain reaction testing, despite extreme prematurity. However, it appears that severe maternal COVID-19 may have been associated with extremely preterm delivery, based on observed histologic chorioamnionitis. This is the first reported case of an extremely preterm infant born to a mother with severe COVID-19 pneumonia who required intubation, and was treated with hydroxychloroquine, azithromycin, remdesivir, tocilizumab, convalescent plasma, inhaled nitric oxide, and prone positioning for severe hypoxemic respiratory failure prior to and after delivery of this infant. The infant remains critically ill with severe respiratory failure on high-frequency ventilation, inotropic support, hydrocortisone for pressor-resistant hypotension, and inhaled nitric oxide for severe persistent pulmonary hypertension with a right to left shunt across the patent ductus arteriosus and foramen ovale. Pregnant women or women planning to get pregnant should take all precautions to minimize exposure to SARS-CoV-2 to decrease adverse perinatal outcomes.